Microsphere distribution and radiation dosimetry in human liver following Yttrium-90 microsphere therapy. - Campbell, Andrew M. (Curtin University, 2000)
The microscopic distribution of microspheres and the resulting radiation dose deposition patterns in human liver following hepatic arterial infusion of 90Y labelled microspheres have been investigated. Tissue samples from normal liver, the tumour periphery and tumour centre were taken from a patient following infusion of 3 GBq of 32 pm diameter resin microspheres labelled with 90Y as treatment for an 80 millimetre diameter metastatic liver tumour. Microspheres were found to deposit inhomogeneously in tissues, preferentially lodging in a region approximately 6 mm wide around the periphery of the tumour. A relative concentration of microspheres of 50 to 70 times that of normal hepatic parenchyma and 65 to 94 times that in the tumour centre was measured in this region. The deposition of microspheres in the tumour periphery was not uniform, and cluster analysis showed that the spheres could be classified into clusters. The number of microspheres in a cluster was skewed towards low numbers and cluster sizes varied from 20 pm to 1500 pm. Microsphere deposition in normal liver was demonstrated to be non-uniform, there being significant variations in concentration over distances on the order of 3 to 4 millimetres. The observed microsphere distributions in three dimensions were used to calculate radiation dose patterns, and the results showed that heterogeneous doses were delivered to all tissues. Within the tumour periphery average doses ranged from 200 Gy to 600 Gy with minimum doses between 70 Gy and 190 Gy. The maximum and minimum doses for the tumour centre sample were 920 Gy and 3.7 Gy respectively, the median dose was 5.8 Gy. In the normal liver sample the median dose was 7.3 Gy with maximum and minimum doses of 753 Gy and 5 Gy respectively. Less than 1% of the normal liver tissue volume received more than 30 GY, the level above which complications have resulted for whole liver exposure using external beam radiotherapy. These calculations suggest that preferential deposition of microspheres in the well vascularised periphery of large tumours will lead to a high proportion of the tumour volume receiving a therapeutic dose, with most of the normal liver tissue being spared substantial damage.